Astrological Practices of Newar Buddhist Community of Kathmandu Valley - Shrestha, Chandan Bade (Journal of Buddhist Studies (T.U.), 2024)
Divination and electional astrology are long-standing practices in the Newar Buddhist community. Though most of the astrological works are ascribed to the elites of the community- the Vajracharya priests, many lay people also have basic skills in using the almanac to find auspicious dates and Newari festivals. While conducting a comprehensive literature review, I discovered that astrological traditions evolved within the Indian subcontinent primarily serve as the foundation of astrological practices of the Newar Buddhist community. Variations exist in the focus during predictions, with an emphasis on Yogini dasha and the inclusion of unique Buddhist nomenclature for planets. In essence, the foundation of these practices lies in a blend of Indic, Tantric, and Buddhist influences. Buddhists historically drew astrological insights from Mahayana texts like ’Sardulakarnavadana’ and ’Mahasamnipata,’ incorporating astral knowledge from Vedic and other Indian astrology systems. The ’Grahamatrika Dharani,’ a key Buddhist text on astrological remedies gained widespread use in the 9th and 10th centuries in Northern India, Nepal and Tibet, sharing similarities with Hindu Navagraha Puja. My exploration also encompasses the timing of significant Newar Buddhist rituals, festivals, fasts, and life events, shedding light on the community’s astrological practices.